Antibacterial Efficacy of Conventional Versus Herbal Products on Streptococcus mutans in Adult Population- a Systematic Review & Meta-analysis - Teja, Kavalipurapu Venkata; Kaligotla, Apoorva Vasundhara; Gummuluri, Sriram (Brazilian Dental Science, 2020)
Background: Dental caries is challenging infectious disease, which is wide spread and difficult to control. Although it’s multifactorial, microorganisms especially cariogenic Streptococcus mutans plays a wide role in initiation and progression of dental caries. Objective: The present review mainly aimed to evaluate and assess the antibacterial efficacy of herbal versus conventional products on Streptococcus mutans. Data Sources: A search was execute in electronic database (i.e., PUBMEDCENTRAL, COCHRANE, LILAC, SCIENCEDIRECT, GOOGLE SEARCH) using following search terms alone and in combination by means of PUBMED search builder from January 1990 up to July 2019. Study Eligibility Criteria: Studies were stipulate if they met the following criteria: In vivo studies comparing herbal and conventional products on anticariogenic or antibacterial activity on Streptococcus mutans were selected. Participants and Intervention: Adult patients aged from 18-65 years with dental caries undergoing intervention of herbal products. Study Appraisal and Synthesis Material and Methods: Out of 225 studies collected from databases, only 6 studies were included and other 6 were collected by hand search. Finally 12 included studies were analyzed out of which 5 studies were considered for meta-analysis. Results: The results unveil that natural products exerted virtually homogeneous antibacterial effect against Streptococcus mutans when compared with the counterpart. Limitations: Review was assessing on patients with dental caries and studies previously assessed did not mention about the caries risk. Prevalence varies based on caries risk assessments. Study was concentrating only on single species Streptococcus mutans. But ideally caries is multifactorial. Conclusion: Although natural products were effective, the present systematic review does not furnish concrete evidence to a show increased antibacterial efficacy of natural products as compared to conventional products. Keywords Antibiotics, Chlorhexidine, Dental Caries, Herbal, Streptococcus mutans.